2020
DOI: 10.1177/0896860820923461
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous mycobacteria infections of peritoneal dialysis patients: A multicenter study

Abstract: Objectives: Nontuberculous mycobacteria (NTM) infections pose a diagnostic challenge in peritoneal dialysis (PD) patients. In this study, we sought to identify findings that are suggestive of NTM infection in PD adult patients. Methods: All patients with NTM exit-site infection (ESI) with/without tunnel infection and peritonitis identified during the last decade in eight medical centers in Israel were included. Clinical, microbiological, and outcome data were collected and analyzed. Results: Thirty patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
(36 reference statements)
0
16
0
2
Order By: Relevance
“…In addition to our suggestion to remove PD catheters for the treatment of NTM, previous studies showed that less than 20% of patients could be resumed on PD. 383 386,390…”
Section: Subsequent Management Of Peritonitismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to our suggestion to remove PD catheters for the treatment of NTM, previous studies showed that less than 20% of patients could be resumed on PD. 383 386,390…”
Section: Subsequent Management Of Peritonitismentioning
confidence: 99%
“…[383][384][385] Published case series have highlighted the pitfall of late NTM diagnosis, with a median delay ranging from 6 to 30 days. 384,386 Given the chance for these organisms to be mistaken for diphtheroids or Corynebacterium species on Gram stain, examination for acid-fast bacilli by Ziehl-Neelsen staining should be requested on peritoneal dialysate fluid. Negative cultures with persistent symptoms of peritonitis, often with concomitant exit-site infection, should also raise concern for the possibility of NTM infection.…”
Section: Non-tuberculous Mycobacterial Peritonitismentioning
confidence: 99%
“…In majority of the cases, the PD effluent WCC at peritonitis onset was slightly elevated. At least half of the patients showed a polymorphonuclear predominance, which is in accordance with the manifestation of other PD-related NTM peritonitis [ 4 ] and may distinguish from tuberculous peritonitis [ 16 ]. AFB smear was positive in 6 patients.…”
Section: Discussionmentioning
confidence: 53%
“…Data on PD-related NTM peritonitis is increasing, however, majority of the cases are caused by rapidly growing mycobacteria such as M. fortuitum and M. abscessus , etc. [ 4 , 5 ], while MAC and other slowly growing NTM-related peritonitis in PD population has rarely been reported. Song et al reviewed 57 episodes of PD-associated NTM peritonitis, and found that MAC was responsible for only 6 episodes [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Present series Bnaya et al 11 Washida and Itoh 12 Jiang et al 13 Song et al subsequent peritonitis. The ever-increasing age, medical complexity and frailty of the patient cohort may also contribute to the increased risk for exit site infection.…”
Section: Referencementioning
confidence: 83%